2017
DOI: 10.1088/1742-6596/908/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

A review on mode-I interlaminar fracture toughness of fibre reinforced composites

Abstract: The effect of plasticity to interlaminar fracture toughness of adhesive bond of composite V Pavelko, K Lapsa and P Pavlovskis Abstract.Composite material has been growing rapidly throughout the year for its unique properties in comparisons with metal. Recently, there has been a growth on studying the way to reduce the delamination failure, which is the primary challenge on laminated fibre composite. This failure can degrade the strength of composite materials, hence loses its function. In this review, databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…212% and 191% for S + C compared to J and S nonhybrid composites. The results are in agreement with results from the literature [27,28,30], where the hybridization of nonhybrid composites also provided an improvement in the G Ic . It was shown in the literature that the type of fiber (natural or synthetic), polymer matrix, stacking sequence and number of layers have significant influences on the mechanical properties (e.g., tensile and flexural strength, impact energy and fracture toughness) of hybrid composites [15,17,24,27,28,30].…”
Section: Dcb Testssupporting
confidence: 92%
See 1 more Smart Citation
“…212% and 191% for S + C compared to J and S nonhybrid composites. The results are in agreement with results from the literature [27,28,30], where the hybridization of nonhybrid composites also provided an improvement in the G Ic . It was shown in the literature that the type of fiber (natural or synthetic), polymer matrix, stacking sequence and number of layers have significant influences on the mechanical properties (e.g., tensile and flexural strength, impact energy and fracture toughness) of hybrid composites [15,17,24,27,28,30].…”
Section: Dcb Testssupporting
confidence: 92%
“…There are a number of studies in the literature that focus on fracture characterization of NRFCs [27][28][29][30]. Nasuha et al [27] reviewed some of these studies on hybridization of composites (e.g., silanized jute/epoxy, carbon/epoxy, silk/ polyester, E-glass/vinyl ester, etc.) using different layers and stacking sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have been done to find the effect of weave pattern on fracture toughness (GIC) of laminated composites by mode I fracture toughness test, and it showed some significant influence [11,170]. Suppakul and Bandyopadhyay [11] compared the mode I fracture toughness of twill, satin and plain weave laminates and reported that twill weave showed the highest GIC value followed by satin and plain weave, respectively.…”
Section: Factors Effecting Mode I Fracture Behaviourmentioning
confidence: 99%
“…In addition to the impact resistance, the effects of strengthening interlaminar fracture toughness of Z-pin composites in mode I, mode II, and mixedmode loading were also studied. [7][8][9][10] Some scholars have explored the reduction of in-plane mechanical properties caused by microstructural damage during the Z-pin insertion process. 11 However, the penetration mechanism during Z-pin insertion into prepreg is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%